Managerial economics theory and practice - Adams, Alix (Elsevier, 2012)
Managerial economics is the application of economic theory and quantitative methods (mathematics and statistics) to the managerial decision-making process. This book will appeal to students with limited prior training in economics and quantitative methods. It assumes that students will have had mathematics training at least through pre-calculus and that they have had a course in elementary statistics. It also expects students to have had an undergraduate course in intermediate microeconomics. The book includes these features: an Online Instructor's Manual; an Online Study Guide; a problem-solving approach to the study of managerial economics that combines the features of a standard managerial economics textbook with those of a separate study guide; a method for helping business students develop the analytical skills necessary for success in the study of managerial economics, finance, and management; and, a more extensive review of mathematical techniques than most comparable textbooks